2006
DOI: 10.1002/path.1950
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of regulatory NKT lymphocytes ameliorates non-alcoholic steatohepatitis and glucose intolerance in ob/ob mice and is associated with intrahepatic CD8 trapping

Abstract: The aim of this study was to determine the effect of adoptive transfer of regulatory natural killer T (NKT) lymphocytes on the metabolic disorder in leptin-deficient ob/ob mice, which feature depletion and defective function of NKT and CD4 lymphocytes. Leptin-deficient ob/ob mice were subjected to transplantation of 1 x 10(6) of either ob/ob or wild-type-derived NKT lymphocytes, or to transplantation of either ob/ob or wild-type-derived splenocytes. The effect on hepatic fat content was measured by magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
2
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 47 publications
0
76
2
3
Order By: Relevance
“…For example, iNKT cells have been shown to drive hyperlipidemia and atherosclerosis but protect from hepatic steatosis (32,(59)(60)(61)(62). Although the effects of MTP deficiency on lipoprotein metabolism are sufficient to explain both lack of atherosclerosis and frequent hepatic steatosis in ABL (1), it is possible that CD1 and NKT dysfunction may contribute to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…For example, iNKT cells have been shown to drive hyperlipidemia and atherosclerosis but protect from hepatic steatosis (32,(59)(60)(61)(62). Although the effects of MTP deficiency on lipoprotein metabolism are sufficient to explain both lack of atherosclerosis and frequent hepatic steatosis in ABL (1), it is possible that CD1 and NKT dysfunction may contribute to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been demonstrated that the aforementioned effects of NKT cell deletion on metabolism can only occur in the absence of CD8 + T cells [66]. Moreover, previous studies have reported that adoptive transfer or agonist activation of NKT cells ameliorate the metabolic dysregulation of the ob/ob mice [55,67], suggesting that the role of NKT cells in obesity-related inflammation may be complex.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Les resultats sont spectaculaires puisque seulement 12 jours apres le transfert on constate une diminution de la steatose, une amelioration des transaminases hepatiques, reflet de l'atteinte hepatique, ainsi qu'une amelioration de la tolerance au glucose. La restauration du nombre de lymphocytes NKT permet donc de moderer la steatose et la sensibilite au glucose dans des etudes a court terme (Elinav et al, 2006). Il est egalement possible de restaurer un nombre de cellules NKT hepatique par des traitements chez la souris.…”
Section: Les Lymphocytes Nktunclassified